SHANXIHIPPUS DERMATORHINUS COMB. NOV. WITH COMPARISONS TO OLD WORLD HIPPARIONS WITH SPECIALIZED NASAL APPARATI (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2018)
Skulls, mandibles and dentitions of a new, monospecific lineage of late Miocene Chinese hipparionine horse, Shanxihippus dermatorhinus nov comb.are reported. We frame our description of this newly recognized genus with a comparison to primitive North American hipparion, Cormohipparion occidentale and Central European Hippotherium primigenium from the Vienna Basin and Hoewenegg, Germany. We recognize, for the first time that the Chinese early late Miocene hipparion “Hipparion” weihoense is primitive and referable to Hippotherium extending the range of that lineage in the early late Miocene (MN9 equivalent) from China to Central and Western Europe. We develop a multistate 53 character state analysis including primitive species of Hippotherium, Sivalhippus, Shanxihippus, Cremohipparion and Proboscidipparion to undertake a cladistic analysis using four consecutively further removed North American outgroups: Cormohipparion occidentale, Cormohipparion quinni, Merychippus insignis and Parahippus leonensis. We evaluate the phylogenetic relationships of these taxa and pose hypotheses of origin and biogeographic distribution of these superspecific taxa in the late Miocene of Eurasia. We conclude that Shanxihippus, Cremohipparion and Proboscidipparion are three distinct clades, held at Genus rank, that have converged in their snout lengthening and nasal retraction likely due to similarities in feeding adaptation.